Narratives and invisible trajectories. The school memory and the students of the National School of Mar del Plata (Praxis Educativa, 2017)
This article aims at highlighting the possibilities of (re)constructing a history of education around the category of School Memory, which emphasizes a look within educational institutions and relies on testimonies, (auto) biographies and school files and records. We begin by defining School Memory in terms of related categories, texts and constituting experiences; then we show the interplay of such concept with the identification of the students in a National High School. From these analyses we have been able to conclude that, although High Schools used to represent “traditional”, “selective” and “elitist” teaching, in practice they served as open spaces for the access of different social classes—actually, they exercised a wider appeal than that which is described in the literature of the time. Eventually, we reflect upon the role of narrative in the field of education, venturing School Memory as the territory which enables the recovery of experiences and argumentative plots and make other educational practices possible.
Keywords: narrative; school memory; high school; national high schools